Integrating Ethnomathematics into Mobile Learning: The Effect of Senimatika on Junior High School Students' Problem-Solving Abilities - Melania Eva Wulanningtyas; Ardhika Fajar Ramadhan; Satriya Ary Hapsara (FKIP Universitas Lampung, 2026)
This study aims to develop and describe the characteristics, feasibility, practicality, and effectiveness of Senimatika, an Android-based mathematics learning media integrated with an ethnomathematics approach to support junior high school students’ mathematical problem-solving skills, particularly in understanding the problem, devising a solution plan, carrying out the plan, and reviewing or verifying the solution. The development of Senimatika was driven by the need for contextual learning media that connect mathematical concepts with students’ cultural backgrounds. The research employed the ADDIE development model, consisting of the Analyze, Design, Develop, Implement, and Evaluate stages. The final product, Senimatika, presents ethnomathematics-based content through interactive features, contextual problem-solving tasks, and culturally relevant visual designs. Data were collected using expert validation questionnaires, student response questionnaires, pretest, and post-test instruments. The validity analysis using Aiken’s V indicated that Senimatika is valid for instructional use, with material experts’ ratings classified as “High Validity” ( ) and media experts’ ratings classified as “Moderate Validity” ( ). These results demonstrate that the product is valid and feasible for use in mathematics learning. Furthermore, student response data revealed a score of 85.86, categorized as “Very Good”, indicating that Senimatika is practical, enjoyable, and easy to use. In terms of effectiveness, the Wilcoxon signed-rank test showed a statistically significant improvement in students’ mathematical problem-solving abilities ( , ). The effect size analysis yielded a moderate effect ( ), confirming the positive impact of Senimatika on students’ learning outcomes. Overall, this study concludes that Senimatika is an innovative, effective, and culturally responsive learning media that enhances students’ engagement and mathematical problem-solving skills by integrating local cultural elements into digital learning environments. Keywords: learning media, android, ethnomathematics, geometric transformation, mathematical problem-solving.